ABORSI DAN HAK ATAS PELAYANAN KESEHATAN: Sebuah Tinjauan Teologis, Yuridis, dan Medis (IAIN Ponorogo, 2012)
ABORSI DAN HAK ATAS PELAYANAN KESEHATAN:Sebuah Tinjauan Teologis, Yuridis, dan MedisÂ Alibaâul ChusnaÂ Abstract: Abortion, at this contemporary era, is fiercely controversial issue for amount of people. Nevertheless, It is a health problem of so many society cause not only diseases but also motherâs death. Abortion is also supposed to be one of several factors for rising motherâs death in Indonesia. It happens because of cases; it can be medical or non-medical motive. Abortion which is medical motive is permitted for prerequisites. Otherwise Abortion which is non-medical motive such as sex harassment pregnancy is not permitted by both Islamic jurisprudence and legal law. But in fact, amount of abortion cases are due to non-medical motives. This paper tries to explore and describe abortion and its connection to health service rights.Â Â Â Â Â Â Â Â Â Â Â Â Keywords: Aborsi, hak, pelayanan kesehatan